Pengaruh Affect of Service, Information Control, Library as Place, dan Library Image terhadap Loyalitas Pengguna Layanan Perpustakaan Nasional dengan Kepuasan sebagai Pemediasi: Pengaruh Affect of Service, Information Control, Library as Place, dan Library Image terhadap Loyalitas Pengguna Layanan Perpustakaan Nasional dengan Kepuasan sebagai Pemediasi - Utami, Novi Prasetyo; Darmanto, Darmanto; Warokka, Ari (Institut Agama Islam Negeri (IAIN) Curup, 2024)
Measuring service quality and public satisfaction is important to support the sustainability of an organization. Excellent service will foster user satisfaction and loyalty. The measuring of service quality in the library uses LibQual method which consists of affect of service variable, information control variable, and library as place variable. In this study, the researcher added one more variable, namely library image. This study was conducted to determine the effect of the four variables on the satisfaction and loyalty of users of the National Library services. The research method used is quantitative causality. Testing the causel relationship between affect of service, information control, library as place, library image, satisfaction, and loyalty factors using the Structural Equation Modeling-Partial Least Square (SEM-PLS) approach. From the results of the direct hypothesis testing, it can be seen that the affect of service and library image factors have an effect on satisfaction, while information control and library as place do not affect satisfaction. Likewise, the satisfaction variable has an effect on loyalty. From the indirect hypothesis testing (mediation), it was found that satisfaction can mediate the affect of service and library image factors on user loyalty, while satisfaction cannot mediate the information control and library as place factors on satisfaction. The results of the study are expected to provide an empirical basis in the development of LibQual theory and a managerial basis for public services at the National Library.